A Detailed Analysis of the Factors Influencing Neonatal TSH: Results From a 6-Year Congenital Hypothyroidism Screening Program - Di Dalmazi, Giulia; Carlucci, Maria Assunta; Semeraro, Daniela; Giuliani, Cesidio; Napolitano, Giorgio; Caturegli, Patrizio; Bucci, Ines (Frontiers in Endocrinology, 2020)
Background: Neonatal thyrotropin (TSH) on dried blood spot (DBS), the most common screening strategy for primary congenital hypothyroidism (CH), is influenced by numerous factors that may hinder a true CH diagnosis. A second test can thus be performed to clarify the initial findings, although its application varies among screening programs. Objectives: The aim of this study was to evaluate the effect of maternal and neonatal factors on neonatal TSH levels and offer practical screening recommendations. Methods: We retrospectively analyzed screening data of 62,132 neonates born in Abruzzo, an Italian region considered mildly iodine deficient, between 2011 and 2016. We then performed a multiple linear regression to model the relationship between TSH (the dependent variable) and 13 independent variables extracted from blood collection cards. Results: Most neonates (53,551 of 62,132, 86%) had normal TSH and no clinical indications for a second screening. A minority (1,423, 2.3%) had elevated TSH in the initial DBS, which was confirmed in 97 cases (7%) on a second screen. The remaining neonates (6,594, 10.6%) had a normal initial TSH but underwent a second test in accordance with screening protocols, and were found to have delayed TSH elevation in 23 cases (0.4%). Those 120 newborns (97 + 23), considered highly suspicious for primary CH, were referred to a pediatrician for confirmatory testing and excluded from subsequent analysis of factors influencing TSH levels. Sex (beta regression coefficient =1.11 female to male, 95 % CI 1.09, 1.12) and age at collection (beta= 0.78 day 5 to days 2-3, 95 % CI 0.74, 0.83) affected neonatal TSH, suggesting the utility of specific nomograms. In addition, prematurity (beta= 0.85 term to preterm, 95 % CI 0.80, 0.91), dopamine use (beta= 0.71, 95 % CI 0.62, 0.81), and birth weight (beta= 1.40 normal versus very low, 95 % CI 1.05, 1.89) strongly influenced neonatal TSH. Conclusions: Neonatal TSH is influenced by several factors supporting the delineation of local sex- and age-adjusted TSH cutoffs, and the universal adoption of a second TSH test in neonates at risk for a missed primary CH diagnosis.